Barbiturate interactions at the human GABAA receptor: dependence on receptor subunit combination. - Thompson, S. A. (1996)
1. Human GABAA receptors containing different alpha and beta subunits with a gamma 2s subunit were expressed in Xenopus oocytes and the effects of pentobarbitone on these subunit combinations were examined by electrophysiological recording of GABA currents with the two-electrode voltage-clamp method. 2. Pentobarbitone has previously been shown to have three actions on GABAA receptors: a potentiation of GABA responses, a direct activation of GABAA receptors and, at high concentrations, a block of the GABA chloride channel. In this study pentobarbitone activity consisted of the above mentioned three components on all the subunit combinations tested. However, the affinities and efficacies varied with receptor subtype. 3. Potentiation of GABA by pentobarbitone occurred over the same concentration-range for all the subunits with affinities in the range of 20-35 microM. The degree of potentiation obtained, however, varied from 236% of GABA EC20 on alpha 1 beta 2 gamma 2s to 536% on alpha 6 beta 2 gamma 2s. 4. Examination of the direct effect of pentobarbitone revealed that the type of alpha subunit present determines both the degree of affinity and efficacy obtained. Receptors containing an alpha 6 subunit produced maximum direct responses to pentobarbitone larger than that obtainable with maximum GABA (150% to 170% of maximum GABA). The maximum direct pentobarbitone response obtainable with other alpha subunits ranged between 45% of maximum GABA for alpha 5 beta 2 gamma 2s to 82% for alpha 2 beta 2 gamma 2s. The affinity of the direct action of pentobarbitone on alpha 6 beta 2 gamma 2s was 58 microM compared to affinities for the other alpha subunits ranging from 139 microM on alpha 2 beta 2 gamma 2s to 528 microM on alpha 5 beta 2 gamma 2s. 5. The type of beta subunit present did not influence the direct action of pentobarbitone to the same extent as the alpha subunit. There were no significant differences between affinity or efficacy on oocytes expressing alpha 6 and gamma 2s with beta 1, beta 2 or beta 3. Affinities and efficacies on oocytes expressing alpha 1 and gamma 2s with beta 1, beta 2 or beta 3 were significantly different with pentobarbitone having a higher affinity and efficacy on alpha 1 beta 3 gamma 2s followed by alpha 1 beta 2 gamma 2s and then alpha 1 beta 1 gamma 2s. 6. The direct effect of pentobarbitone was blocked by picrotoxin but not by competitive antagonists, such as bicuculline or SR95531, indicating that the direct agonist activity of pentobarbitone was not mediated via the GABA binding site. 7. For the first time the influence of the various alpha and beta subunits on the effects of pentobarbitone were demonstrated. The results indicate that GABAA receptors containing alpha 6 subunits have both a higher affinity and efficacy for direct activation by pentobarbitone, and reveal that pentobarbitone binds to more than one site on the GABAA receptor, and these are dependent on receptor subunit composition.